2021
DOI: 10.3390/foods10112822
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Traits, Meat Quality, and Volatile Compounds of Lamb Meat from Different Restricted Grazing Time and Indoor Supplementary Feeding Systems

Abstract: This study was conducted to investigate the carcass traits, meat quality, and volatile compounds of growing lambs under different restricted grazing time and indoor supplementary feeding systems. Fifty 3-month-old male Tan lambs (with similar body weight) were divided into five groups randomly according to grazing time 12 h/d (G12), 8 h/d(G8), 4 h/d(G4), 2 h/d (G2), and 0 h (G0, indoor supplementary feeding). Animals were slaughtered at the end of the experiment, and the longissimus thoracis (LT) samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 71 publications
0
38
0
Order By: Relevance
“…Meat flavor is determined largely by VFCs, which are mainly generated from lipids and water-soluble compounds via the Maillard reaction and lipid oxidation upon processing [ 43 ]. Here, we identified 25 VFCs, with the largest proportion being aldehydes; this was the same as that of other VFCs in meat [ 44 , 45 ]. Because of their low odor detection threshold, aldehydes greatly affect the aroma of cooked meat [ 46 ].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Meat flavor is determined largely by VFCs, which are mainly generated from lipids and water-soluble compounds via the Maillard reaction and lipid oxidation upon processing [ 43 ]. Here, we identified 25 VFCs, with the largest proportion being aldehydes; this was the same as that of other VFCs in meat [ 44 , 45 ]. Because of their low odor detection threshold, aldehydes greatly affect the aroma of cooked meat [ 46 ].…”
Section: Discussionmentioning
confidence: 57%
“…Heptanal is mainly produced by oxidation of linoleic acid and has been shown to be a key volatile compound in previous studies [ 41 ]. Ketones are mainly formed by oxidation of fatty acids, with obvious milk or fruit flavors, a relatively high odor threshold, and a lesser contribution to meat aromas [ 45 ]. We found that 2-butanone was differentially expressed in the three mutton hybrids and is usually considered to be a product of the Maillard reaction [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the results obtained in the present paper are consistent with data reported in previous studies based on the evaluation of the increase in volatile compounds during ageing of beef and lamb [ 57 ]. The increase in volatile compounds during the first week of vacuum aging can be linked to the chemical modifications of fat and protein molecules during storage [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, three main feeding systems are used for feeding livestock: cereals plus forages (mainly barley and alfalfa hay), concentrate pellets plus forages, or complete pelleted diets [ 7 , 8 ]. Moreover, the quantity and quality of feeds are mainly dependent on the type, proportion, and availability of the feedstuffs that are used, as well as the feed processing, all of which can directly affect the changes in growth rate, carcass yield, meat quality, and composition [ 4 , 9 , 10 , 11 ]. Therefore, the objectives of the study were to investigate the effects of different feeding regimes on productive performance, carcass characteristics, meat quality, and fatty acid contents in growing lambs.…”
Section: Introductionmentioning
confidence: 99%